2010
DOI: 10.1242/jeb.038984
|View full text |Cite
|
Sign up to set email alerts
|

The influence of foot posture on the cost of transport in humans

Abstract: SUMMARYAlthough humans appear to be specialized for endurance running, the plantigrade posture of our feet, in which the heel contacts the substrate at the beginning of a step, seems incompatible with economical running. In this study, we tested the hypothesis that plantigrade foot posture reduces the energetic cost of transport (COT) during walking in humans. When human subjects walked with their heels slightly elevated in a 'low-digitigrade' posture, COT increased by 53% above that of normal plantigrade walk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
75
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(88 citation statements)
references
References 42 publications
3
75
1
2
Order By: Relevance
“…Humans represent an exception to this pattern (Cunningham et al, 2010) as we possess adaptations for endurance terrestrial running (Bramble and Lieberman, 2004;Carrier, 1984), combined with plantigrade feet and a prominent heel strike (HS), during walking gaits, where the foot touches down heel first on the calcaneal tuberosity in a dorsiflexed posture, without mid-or forefoot contact. Given the importance of limb length to cursorial mammals, it is uncertain why humans use a plantigrade foot posture with a consistent HS during walking (Cunningham et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Humans represent an exception to this pattern (Cunningham et al, 2010) as we possess adaptations for endurance terrestrial running (Bramble and Lieberman, 2004;Carrier, 1984), combined with plantigrade feet and a prominent heel strike (HS), during walking gaits, where the foot touches down heel first on the calcaneal tuberosity in a dorsiflexed posture, without mid-or forefoot contact. Given the importance of limb length to cursorial mammals, it is uncertain why humans use a plantigrade foot posture with a consistent HS during walking (Cunningham et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies where RE has been measured during different FSP conditions, submaximal VO 2 hasn't differed significantly between FFS and RFS (Ardigo et al, 1995;Cunningham et al, 2010;Perl et al, 2012). In contrast, we found that SI changes in each SR condition showed substantial shifts in FSP and when comparing the difference in VO 2 under the two SR conditions (±10% from preferred) that on average produced the greatest alteration and gap in FSP, we did find significant differences in VO 2 between the -10% SR condition and the +10% condition .…”
Section: Changes In Vo2 From Preferredmentioning
confidence: 86%
“…In studies where RE has been measured during different FSP conditions, submaximal oxygen consumption (VO 2 ) was not different between FFS and RFS (Ardigo, Lafortuna, Minetti, Mognoni, & Saibene, 1995;Cunningham, Schilling, Anders, & Carrier, 2010;Perl et al, 2012). Tartaruga et al (2012) found that distance runners running at the same treadmill speed and the same physiological intensity had SR and internal ankle angles at foot strike (which relate to FSPs) that made up 23% and .6%, respectively, of the biomechanical factors affecting RE.…”
Section: Introductionmentioning
confidence: 99%
“…La falta relativa de pelo en el cuerpo, la capacidad excepcional para sudar y almacenar energía de forma elástica en los músculos y tendones del tobillo 1,2. El consumo aeróbico que manifiesta en las largas distancias, y los dedos del pie más cortos parecen ser adaptaciones para la carrera de resistencia 3 . Además muchos creen que la carrera está en nuestros genes porque el Homo tuvo que correr para alcanzar a la presa antes de la invención de los arcos y las flechas 2 .…”
Section: Introduccionunclassified
“…Es decir, el talón durante la marcha contacta con el suelo y absorbe energía en el inicio de la ejecución del paso; se espera que este mecanismo limite el almacenamiento y la recuperación de energía elástica en los mús-culos extensores de la articulación del tobillo. Este tipo de apoyo nos hace ser andadores económicos pero no corredores económicos 3 . Independientemente del porqué empezamos a correr, es evidente que se hizo sin zapatos; el primer ejemplo de calzado se remonta a más de 10.000 años cerca de Fort Rock.…”
Section: Introduccionunclassified